Exploring disruptive adolescent behaviours on social media: A case study during the times of Crisis - Aliff, Nawi; Nor Yazi, Khamis; Zalmizy, Hussin; Muhammad Noor, Abdul Aziz (Universiti Putra Malaysia, 2023)
Social media usage has been observed to increase in times of crisis, like the COVID-19 pandemic, when it served as the primary means of communication with the outside world. The amplification is hypothesised to cause higher adverse consequences to adolescents with disruptive behaviours. These vulnerable youngsters, characterised by higher negative emotionality, could experience a more unfavourable impact of the media than those with non-disruptive behaviours. However, the extent to which the media can affect disruptive adolescents is unknown. Twenty-one secondary school adolescents identified with several disruptive behaviour records were selected for a survey and online observation of an explanatory mixed-method design. Nine adolescents’ personal Instagram accounts were observed for over three months. The data recorded a medium-high social media use among the respondents, particularly in maintaining existing relationships. There were patterns of oblivious, excessive attention-seeking posts from the qualitative exploration, which conflicts with the adolescents’ weak agreement on using the media to make themselves known. The adolescents’ postings on spiritual advice brought some engrossing tone down of the adolescents’ behaviours. The grounded religious beliefs could be their self-control mechanism when using the media. The echo chamber of their spiritual advice postings and controlled media use could be much-needed interventions for adolescents with disruptive behaviours.